Empowerment through participation in community-based participatory research—effects of a physical activity promotion project among socially disadvantaged women - Röger-Offergeld, Ulrike; Kurfer, Eva; Brandl-Bredenbeck, Hans Peter (Frontiers in Public Health, 2023)
Introduction Community-based participatory research (CBPR) approaches are associated with a range of positive impacts on empowerment. However, only a few studies have investigated the influence of different modes of target group participation on empowerment. The present study examined the empowerment processes and outcomes of women in difficult life situations through their participation as co-researchers in the form of Photovoice in “Stark durch Bewegung” (English: “Strong through Movement”), a CBPR project for physical activity (PA) promotion. The extent to which women’s participation as co-researchers leads to empowerment was compared with other forms of participation. Methods The Photovoice approach consisted of three components: (1) photo task, (2) focus group interviews, and (3) exhibition of photos. It was then extended through participant observation. A total of 18 women took part in Photovoice. They took photos, were involved in four focus groups, helped in the analysis of data, and supported their exhibition. Two additional short focus group interviews in which four more women participated were conducted at the end of the project. The interview guideline was based on the SHOWeD questions proposed within the framework of Photovoice and enriched with various other questions (e.g., self-efficacy, social contacts, and community involvement). The data were analyzed based on a grounded theory approach. Results “Stark durch Bewegung” contributed to women’s empowerment in several ways. By participating in the project’s PA programs, the women reported numerous empowerment effects, such as improved self-efficacy, perceived competencies like swimming and language skills, and social networks. By participating as co-researchers, they perceived empowering processes on organizational and community levels that are comparable with other forms of participation (e.g., participation in a cooperative planning group) but also differ from them at relevant points (e.g., encouraging them to reflect on their own PA behaviors). The willingness to get involved in Photovoice was estimated to be significantly higher than in other possible forms of participation. Conclusion Our findings support the notion that health promotion interventions with marginalized groups can contribute to their empowerment on multiple levels when participants become equal partners in the CBPR project. Involving women as co-researchers has advantages over other forms of participation in terms of their empowerment.